2020
DOI: 10.1111/jpn.13290
|View full text |Cite
|
Sign up to set email alerts
|

A novel polysaccharide isolated from Flammulina velutipes, characterization, macrophage immunomodulatory activities and its impact on gut microbiota in rats

Abstract: The structural characteristics of a novel Flammulina velutipes polysaccharide (FVP2) were explored in this study. Besides, immunomodulatory activities of FVP2 on RAW 264.7 cell and its impact on gut microbiota in rats were investigated. FVP2 has a molecular weight of 18.3 kD, and its main components include galactose (19.96%), glucose (60.66%) and mannose (19.38%). By NMR analysis, the main‐chain structure consisted of (1 → 3)‐linked‐β‐D‐Gal, (1 → 6) ‐linked‐β‐D‐Gal, (1 → 6)‐linked‐α‐D‐Glc and (1 → 3,6)‐linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Flammulina velutipes is one of the most popular edible mushrooms that contain triterpenes, polysaccharides, sterols and vitamins. F. velutipes polysaccharides have anti-inflammatory, antioxidant, anti-aging, immune modulatory, and intestinal flora activities (7)(8)(9)(10). Earlier experiments of our group found that F. velutipes polysaccharides were non-toxic and could promote intestinal motility and improve constipation in rats (11).…”
Section: Introductionmentioning
confidence: 94%
“…Flammulina velutipes is one of the most popular edible mushrooms that contain triterpenes, polysaccharides, sterols and vitamins. F. velutipes polysaccharides have anti-inflammatory, antioxidant, anti-aging, immune modulatory, and intestinal flora activities (7)(8)(9)(10). Earlier experiments of our group found that F. velutipes polysaccharides were non-toxic and could promote intestinal motility and improve constipation in rats (11).…”
Section: Introductionmentioning
confidence: 94%
“…For example, in vitro fermentation of polysaccharide from the seeds of Plantago asiatica L. showed that acetic and butyric acids are produced mainly due to the fermentation of aldehydes and xylose, whereas propionic acid is mainly generated by fermentation of arabinose and xylose ( 71 ). Flammulina velutipes polysaccharide with the monosaccharide composition at the ratio of glucose: galactose: mannose = 60.66:19.96:19.38 can increase the levels of isobutyric and butyric acid ( 72 ). On the contrary, the Flammulina velutipes polysaccharide with the monosaccharide composition at the ratio of mannose: glucose: xylose: arabinose: fucose = 6.6:27.8:18:1.5:5.2 increased the levels of acetic, propanoic and butyric acids ( 73 ).…”
Section: Gut Microbiota Metabolites Modulated By Dietary Compoundsmentioning
confidence: 99%
“…In summary, PEP intake could play a positive role in gastrointestinal health [ 216 ]. Also, a separately published report revealed evidence that a novel polysaccharide (FVP2) isolated from Flammulina velutipes , impact on gut microbiota in rats was reported by Jufeng Ye [ 94 ]. On the one hand, the concentrations of two short-chain fatty acids (isobutyric acid and butyric acid) and the abundance of beneficial bacteria in the caecum after the FVP2 treatment were significantly higher than those in control group, as well as butyric acid level was effectively improved, thus increasing the intestinal beneficial bacteria.…”
Section: Antiviral Mechanisms Of Emfs Polysaccharidesmentioning
confidence: 99%
“…On the one hand, the concentrations of two short-chain fatty acids (isobutyric acid and butyric acid) and the abundance of beneficial bacteria in the caecum after the FVP2 treatment were significantly higher than those in control group, as well as butyric acid level was effectively improved, thus increasing the intestinal beneficial bacteria. On the other hand, FVP2 can maintain the integrity of intestinal mucosa by improving intestinal barrier function [ 94 ].…”
Section: Antiviral Mechanisms Of Emfs Polysaccharidesmentioning
confidence: 99%